2010
DOI: 10.1002/adma.201000171
|View full text |Cite
|
Sign up to set email alerts
|

Current‐Injected Spectrally‐Narrowed Emissions from an Organic Transistor

Abstract: A novel organic LEFET device with a simple device constitution is presented. The device is equipped with a diffraction grating that is formed on the gate insulator so that it is located outside the channel region. When the device is operated with square‐wave alternating gate voltages, the spectrally‐narrowed emissions are definitively observed with FWHM ∼2 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 24 publications
1
71
2
Order By: Relevance
“…In the previous studies we reported the current-injected SNE from the OLEFETs where an organic crystal was laminated on top of a diffraction grating that was a part of the gate insulator [3,4]. Meanwhile, we have confirmed that the strong light emission arises from the OLEFETs using a layered structure of p-and n-type organic crystals [5].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the previous studies we reported the current-injected SNE from the OLEFETs where an organic crystal was laminated on top of a diffraction grating that was a part of the gate insulator [3,4]. Meanwhile, we have confirmed that the strong light emission arises from the OLEFETs using a layered structure of p-and n-type organic crystals [5].…”
Section: Introductionsupporting
confidence: 79%
“…The grating formed a gate insulator together with the SiO 2 layer. The direction along the channel width was rotated 14 • clockwise from the direction connecting and M. The current-injected emissions were measured in vacuum (∼10 −3 Pa) using the same setup [3,5] and driving circuit [11] described previously. For the measurements, we designated the source (MgAg) and drain (Au) electrodes as the electron-and hole-injection contacts, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Preferably the recombination zone is fixed at a pre-defined position. This would open the possibility to further increase the device light output, for instance, by incorporating optical structures such as a distributed Bragg reflector in the channel [14,15]. Undesired small variability in mobility and threshold voltages of the electrons and holes during fabrication as well as charge-trapping effects during operation make it however difficult to fabricate LEFETs with the recombination zone at a pre-defined position.…”
Section: Recombination Zone In Ferroelectric Lefetsmentioning
confidence: 99%
“…The light output of the LEFETs is yet too low for many practical applications. Several approaches have been proposed to increase the light output by using for instance bilayer structures composed of p-type and n-type semiconductors [6][7][8][9], organic heterostructures in the channel [10,11], improved injection of both carriers by tuning the work functions of injecting contacts [3,12], adding small amounts of semiconducting carbon nanotubes [13], incorporating optical structures [14,15] and multiple gates [16]. The drawback of these methods is that they add complexity to the fabrication process.…”
mentioning
confidence: 99%
“…From the cut-off positions of secondary electron spectra, the work functions of AC5, AC5-CF 3 Thiophene/phenylene co-oligomers (TPCOs) [1][2][3] show excellent electronic and photonic properties in their crystalline states and have attracted much interest as potentially useful organic materials for photonic devices. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Following device applications and observations of phenomena were reported so far: field-effect transistors (FETs), 4-7 light-emitting FETs (LEFETs), 8,9 light emitting diodes (LEDs), 10 photovoltaic cells, 11 photodetectors, 12 current-injected spectrally narrowed emission, 13 and optically pumped lasers. 5,14-17 TPCO crystals are new candidates for achieving current-induced lasing in organic semiconductors.…”
mentioning
confidence: 99%